Dampak Hujan Asam Pada Lingkungan - Mochammad Imam Indra Gumirat; Dodi Satriawan; Dewi Wahyuningtyas (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2021)
The term acid rain refers to the deposition of the atmosphere containing acidic compounds that fall to the earth in the form of rain, snow, particulates, gases and vapors and have a negative impact on the earth. Acid rain was first introduced by Ducros (1845) and later described by the English chemist Robert Angus Smith (1852) whose research studies linked the sources of acid rain to industrial emissions and included early observations of the damaging environmental effects. This article summarizes the scope of acid rain by providing the latest scientific advances on how emissions, deposition, and temporal trends of the pollutants that cause acid rain vary around the world. Considerable progress in reducing SO2 and NOX emissions is evident throughout North America and Europe. In contrast, the decline in SO2 started only about 10 years ago in China and the decline in NOX emissions only in the last few years. While in other parts of Asia such as India, these emissions continue to increase. Investigations of chemical contaminants in surface water, soil, fish, and vegetation show that recovery is slow and will unfold over decades as emissions and depositions continue to decline. Whether the affected ecosystems will return to their current acid rain conditions is uncertain and will likely depend on many other factors such as human disturbance and natural disasters and climate change. Gaining a better understanding of how acid rain interacts with various factors that affect ecosystem trajectories remains a challenge for the scientific community to address.